Designing High-Performance Fuzzy Controllers Combining IP Cores and Soft Processors - Oscar Montiel-Ross; Jorge Quiñones; Roberto Sepúlveda (Advances in Fuzzy Systems)
This paper presents a methodology to integrate a fuzzy coprocessor described in VHDL (VHSIC Hardware Description Language) to a soft processor embedded into an FPGA, which increases the throughput of the whole system, since the controller uses parallelism at the circuitry level for high-speed-demanding applications, the rest of the application can be written in C/C++. We used the ARM 32-bit soft processor, which allows sequential and parallel programming. The FLC coprocessor incorporates a tuning method that allows to manipulate the system response. We show experimental results using a fuzzy PD+I controller as the embedded coprocessor.